Analysis of Variables of Gender, Religiosity, Emotional Intelligence and Allowances for Women's Decisions to Become Leaders - Sokhikhatul Mawadah; Leli Lismay (HUMANISMA : Journal of Gender Studies, 2022)
Some people think that men are the most perfect in terms of leadership. The fact states that in a religious environment, it iswrong for a woman to become a leader. However, at UIN Walisongo Semarang the number of female leaders is quite large. Women with emotional intelligence, the softer and more sensitive feelings they have, can also be one of the determining variables. Emotional intelligence is the ability to control oneself, have endurance when facing a problem, able to control impulses, motivate oneself, able to regulate moods, ability to empathize and build relationships with others. Another variable is about benefits. The existence of allowances is a good wind as additional income for the family's economy/finances. This research uses quantitative research methods. The variables of this study are variable X including: gender, religiosity, emotional intelligence, and benefits, variable Y namely: women's decision to become leaders. The subjects of this study were 45 female respondents, the respondents came from university level administrators, faculty and institutional levels. The data analysis technique uses descriptive analysis and multiple regression analysis. The results of the study stated that there was a significant influence on the variables of gender, religiosity and emotional intelligence on women's decisions to become leaders. Meanwhile, there is no significant influence on the allowance variable on women's decisions to become leaders. In the gender variable, there is an ideological influence of gender roles on providing support to prospective female leaders in student organizations and there are ideological differences in the gender roles of female voters who choose female and male leaders. In the religiosity variable, leaders who have a transformative style who continue to motivate their employees and are supported by a high level of religiosity, the campus will develop and be able to compete well. In the emotional intelligence variable, one of the important factors that influence a woman to become a leader. Women have more empathy and can build better relationships. On the benefits variable, that benefits affect employee performance, but does not affect the decision making of a woman to become a leader.